The PlantPure Nation cookbook : the official companion cookbook to the breakthrough film...with over 150 plant-based recipes - Campbell, Kim (Nutritionist) (BenBella Books, 2015)
"A revolution has begun... From a creative team that includes the producer and writer of Forks Over Knives, the documentary film PlantPure Nation captures the inspiring story of plant-based nutrition's impact on a small town in the rural South and the effort to bring about historic political change. As the film's official companion cookbook, The PlantPure Nation Cookbook brings this powerful, science-based approach to nutrition from the big screen to your kitchen with some of the same mouthwatering recipes that kick-started the revolution, promoting the health benefits of a whole food, plant-based diet. Author Kim Campbell is the wife of PlantPure Nation Executive Producer and Director Nelson Campbell and daughter-in-law of Dr. T. Colin Campbell, coauthor of The China Study and father of the modern plant-based nutrition movement. She is also a culinary contributor, recipe developer, and cooking instructor at Campbell Wellness, a health and wellness business. In PlantPure Nation Cookbook, she shares more than 150 extensively tested, 100% plant-based recipes that she has created and cultivated over 25 years of vegan cooking, such as: Caribbean Quinoa Bowl Buffalo Beans and Greens Edamame Burgers Reuben Potato Bake With a foreword by Dr. Campbell, The PlantPure Nation Cookbook is also filled with tips, tricks, and grocery lists for people interested in a whole food, plant-based diet. And with intimate background and behind-the-scenes details from PlantPure Nation film, this companion cookbook is a must-have for stimulating healthful eating in your home. Join the revolution to jumpstart your health!"--